Creative strategy in advertising - Bonnie L. Drewniany (Thomson/Wadsworth, 2008)
I have had much success with this book. My professor is the editor of a widely read prestigious magazine, and she truly believes in this text. Our class has welcomed many guest speakers in the fields of Advertising, PR, and Design who all reviewed this text and found its contents to support what they practice in their professional work.